2009
DOI: 10.1044/1059-0889(2009/06-0024)
|View full text |Cite
|
Sign up to set email alerts
|

Head Shake Computerized Dynamic Posturography in Peripheral Vestibular Lesions

Abstract: The head shake modification to standard SOT increased the test sensitivity to identification of patients with unilateral, peripheral vestibular hypofunction and those with head movement provoked symptoms. However, this occurred with low specificity, resulting in no significant improvement in overall performance with this head shake protocol. Suggestions for further research to improve the performance of the head shake modification of SOT for clinical application are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 13 publications
4
52
2
Order By: Relevance
“…24 The head shake sensory organisation test was developed partly because of the insensitivity of the sensory organisation test for examining vestibular lesions. 24,25,29,30 The current study revealed no statistically significant difference between the migrainous vertigo group and the migraine without vertigo group on the fixed head shake sensory organisation test. In condition 2 of the sensory organisation test, participants are required to stand on a firm surface with their eyes closed.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…24 The head shake sensory organisation test was developed partly because of the insensitivity of the sensory organisation test for examining vestibular lesions. 24,25,29,30 The current study revealed no statistically significant difference between the migrainous vertigo group and the migraine without vertigo group on the fixed head shake sensory organisation test. In condition 2 of the sensory organisation test, participants are required to stand on a firm surface with their eyes closed.…”
Section: Discussioncontrasting
confidence: 51%
“…In contrast to these findings, Mirsha et al, in a study comparing participants with normal and abnormal vestibular systems, found good specificity and poor sensitivity for condition 2, but found the opposite for condition 5. 25 The head shake sensory organisation test has not been employed in studies of migraine or migrainous vertigo.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations